Safety and Efficacy of a New Renal Denervation Catheter in Hypertensive Patients in the Absent of Antihypertensive Medications: A Pilot Study. (14th February 2019) - Li, Yang; Nawabi, Abdul Qadir; Feng, Yi; Dai, Qiming; Ma, Genshan; Liu, Naifeng
Abstract : Aim . The aim of present study was to determine the safety and efficacy of a new renal artery denervation system for treatment of hypertensive patients. Methods . Hypertensive patients with mean office systolic blood pressure ≥150mmHg and ≤180mmHg or an average of 24-hour ambulatory systolic blood pressure ≥145mmHg and ≤170mmHg after stopping hypertensive medications for 2 weeks or more were enrolled to undergo renal denervation (RDN) using a new RDN system. Changes in office blood pressure and mean 24-hour ambulatory blood pressure and safety were assessed after 6 months. Results . Fifteen patients underwent RDN and followed up for 6 months. At the 6-month follow-up, office systolic blood pressure decreased 11.5±9.9mmHg (P<0.01) and office diastolic blood pressure decreased 6.9±4.8mmHg (P<0.01); mean 24-hour ambulatory systolic blood pressure decreased 7.5±7.7mmHg (P<0.05) and mean 24-hour diastolic blood pressure decreased 3.3±4.7mmHg (P>0.05) compared to baseline values. There were no serious RDN-related adverse events during follow-up. Conclusion . Our results demonstrate that the new RDN system is safe and could significantly reduce blood pressure in hypertensive patients in the absence of antihypertensive medications. This trial is registered withChiCTR1800017815 .